Structure formation of abrasive-resistant coatings - Savulyak, V.I.; Shenfeld, V.Y.; Shylina, O.P.; Osadchuk, A.A. (Problems of Tribology, 2022)
The paper presents the results of the study of abrasion-resistant coatings obtained by surfacing on alloying compositions Fe-Cr-Mo-V-C and Fe-Cr-B4C-Mo-C.It is established that with the increase of chromium in alloying compositions from 2% to 10%, the hardness and wear resistance of coatings increases due to the formation of a significant amount of complex alloyed carbides.The microhardness of the structural components of the deposited coatings correlates with the percentage of carbido-forming elements. Chromium-based coatings with the addition of vanadium, molybdenum and boron have shown high wear resistance under abrasive wear